2023
DOI: 10.3390/jmse11122325
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Numerical Captive Model Tests for Underwater Vehicles: The DARPA SUB-OFF Test Case

Vito Vasilis Zheku,
Diego Villa,
Benedetto Piaggio
et al.

Abstract: During the early design stage of an underwater vehicle, the correct assessment of its manoeuvrability is a crucial task. Conducting experimental tests still has high costs, especially when dealing with small vehicles characterized by low available budget. In the current investigation, virtual towing tank tests are simulated using the open-source OpenFOAM library in order to assess the reliability of CFD methods for the prediction of hydrodynamic forces and moments. A well-known case study, the Defence Advanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
0
0
Order By: Relevance
“…A large-eddy simulation (LES) was used for a fully appended Joubert BB2 submarine model to complement the experimental investigations of the wake of the hydroplanes and sail [12]. The open-source OpenFOAM library was used for pure drift tests, rudder tests, and pure rotation in both the vertical and horizontal planes of the Defence Advanced Research Projects Agency (DARPA) SUB-OFF model [13]. It was shown that the expected errors between the measured data and the predictions for the fully appended configuration are within 5% for the linear part and 15% for the higher drift angles.…”
Section: Introductionmentioning
confidence: 99%
“…A large-eddy simulation (LES) was used for a fully appended Joubert BB2 submarine model to complement the experimental investigations of the wake of the hydroplanes and sail [12]. The open-source OpenFOAM library was used for pure drift tests, rudder tests, and pure rotation in both the vertical and horizontal planes of the Defence Advanced Research Projects Agency (DARPA) SUB-OFF model [13]. It was shown that the expected errors between the measured data and the predictions for the fully appended configuration are within 5% for the linear part and 15% for the higher drift angles.…”
Section: Introductionmentioning
confidence: 99%